Efficacy of Kinesio Taping compared to other treatment modalities in musculoskeletal disorders: A systematic review and meta-analysis - Tran, L.; Makram, A. M.; Makram, O. M.; Elfaituri, M. K.; Morsy, S.; Ghozy, S.; Zayan, A. H.; Nam, N. H.; Zaki, M. M. M.; Allison, E. L.; Hieu, T. H.; Quang, L. L.; et al. (Research in Sports Medicine, 2023)
Kinesio taping is widely used in musculoskeletal conditions. We performed a systematic review and meta-analysis on the efficacy of kinesio taping in musculoskeletal disorders compared to other interventions. Twelve electronic databases were used for systemic search and data relevant to pain and disability were extracted. The protocol was registered in PROSPERO (CRD42018087606). Meta-analysis was performed to compare the efficacy of kinesio taping to other modalities of musculoskeletal disorders. As a result, 36 studies were included in the quantitative analysis. Kinesio taping was found to provide an improvement of both pain and disability when applied to any region of the body. In the first five days of application, kinesio taping significantly reduced the pain in all body regions (SMD = -0.63, 95%CI: -0.87, -0.39). This was also noted after four-to-six weeks of application (SMD = -0.76, 95%CI: -1.07, -0.45). When kinesio taping was used for disability in low back pain patients, it significantly reduced the disability within five days of application (SMD = -0.70, 95%CI: -1.29, -0.11). Finally, kinesio taping has shown an improvement of the disability in all body regions after four-to-six weeks of application (SMD = -0.59, 95%CI: -0.96, -0.22). Our findings support kinesio taping as an adjuvant to other treatments for musculoskeletal disorders.